2006
DOI: 10.1152/ajpheart.00942.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of endothelial nitric oxide synthase phosphorylation and activity in uterine artery endothelial cells

Abstract: Pregnancy enhanced nitric oxide production by uterine artery endothelial cells (UAEC) is the result of reprogramming of both Ca(2+) and kinase signaling pathways. Using UAEC derived from pregnant ewes (P-UAEC), as well as COS-7 cells transiently expressing ovine endothelial nitric oxide synthase (eNOS), we investigated the role of phosphorylation of five known amino acids following treatment with physiological calcium-mobilizing agent ATP and compared with the effects of PMA (also known as TPA) alone or in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…Such studies showed that the sustained phase of capacitative entry in UAECs is, in fact, not a constant elevation of [Ca 2þ ] i but a repeated periodic increase in [Ca 2þ ] i ([Ca 2þ ] i bursts) [11]. In this study, we further report novel findings from extended simultaneous recordings of individual cells from both NP-UAECs and P-UAECs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Such studies showed that the sustained phase of capacitative entry in UAECs is, in fact, not a constant elevation of [Ca 2þ ] i but a repeated periodic increase in [Ca 2þ ] i ([Ca 2þ ] i bursts) [11]. In this study, we further report novel findings from extended simultaneous recordings of individual cells from both NP-UAECs and P-UAECs.…”
Section: Discussionsupporting
confidence: 55%
“…Prior to stimulation, cells were washed twice and then incubated for 1 h in Krebs buffer, which was then removed and replaced with fresh buffer or with 300 lM (43,37)GAP27 in Krebs buffer. Serum starvation continued for three more hours prior to addition of 1.5 lCi per well of L-[2,3,4,5-3 H]arginine monohydrochloride (61 Ci/mmol; GE Healthcare Bio-Sciences), followed by addition of vehicle or ATP (30 min, final concentration, 100 lM) to the appropriate wells; the assay was then continued as described previously [10,11].…”
Section: Nos3 Activation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…PMA, also known as 12-O-tetradecanoylphorbol-13-acetate (TPA), is a potent tumor promoter often used in biomedical research [27]. Ionomycin is an ionophore produced by Streptomyces conglobatus .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac myocytes express the three isoforms although eNOS is mainly expressed in the endothelial cells. eNOS is constitutively expressed and can be stimulated with the increase of cytosolic calcium and phosphorylation [Cale & Bird, 2006]. In contrast, iNOS is a cytokine-inducible isoenzyme.…”
Section: Introductionmentioning
confidence: 99%